„Der Neurologe hätte die Nervenleitgeschwindigkeit messen müssen.“ – Das kommunikative Aushandeln des Expertenstatus in deutschsprachigen Diskussionsforen der Medizin. - Rentel, Nadine (Linguistik Online, 2017)
In online communication, the social identity of the persons involved is negotiated throughout communication processes with other members of a discourse community. In discussion fora in the domain of medicine, the focus lays on the discussion of the expert status of the users. This contribution aims at describing linguistic strategies that are used in order to create a positive self-image as medical expert in a community of practice. The study is based on a corpus of three selected German discussion fora concerning medical issues. Besides the need to boost the own expert status, we find examples in which users try to attenuate their knowledge claim. The results of the analysis indicate that for the domain of medicine, online and offline reality seem to be closely interwoven.